The Use of a Write-Pair-Square Strategy to Improve The Students’ Active Participation in Writing Descriptive Text - Dwi Arni Siti Margiyanti (UIN Salatiga, 2014)
Many problems faced by students in participating in the classroom and writing a text. This study discussed the use of write-pair-square strategy to improve the students’ active participation in writing descriptive text. The objectives of the study are to find out the implementation of write-pair-square in teaching descriptive text and to investigate the improvement of students’ participation and writing achievement after being taught by using write-pair-square strategy. The research focused on teaching of descriptive text by using write-pair-square as the strategy. The subjects are SMA Kesatrian 2 Semarang students. This study used Classroom Action Research that was carried out through a pre-test, first and second cycle activities. The result showed that the students’ progress of participation improved. The average score of pre-test was 11.27, post-test 1 was 20.13, and post-test 2 was 30.24. It also showed that students’ mastering descriptive improved. The average achievement of students’ pretest was63.27, First cycle test was70.23and post test was 77.66. According to this study, I conclude that teaching descriptive text by using write-pair-square as the strategy is helpful for students. It is recommended for English teachers to use Write-pair-square as the strategy for students’ improvement of their writing skill. Keywords: Teaching Descriptive Text; Write-Pair-Square; Active Participation